2014
DOI: 10.1213/ane.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Preconditioning Inhibits Isoflurane-Mediated Apoptosis in the Developing Rat Brain

Abstract: Background We hypothesized that preconditioning with a short exposure to isoflurane (ISO) would reduce neurodegeneration induced by prolonged exposure to ISO in neonatal rats, as previously shown in neuronal cell culture. Methods We randomly divided 7-day-old Sprague-Dawley rats into 3 groups: control, 1.5% ISO, and preconditioning (PC) + 1.5% ISO. The control group was exposed to carrier gas (30% oxygen balanced in nitrogen) for 30 min and then carrier gas again for 6 h the following day. The 1.5% ISO group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…Most of the previous studies have focused on the anesthetic-induced type 1 cell death (apoptosis), 21,22 but cells can also die from type 2 (autophagic cell death) or type 3 cell death (necrosis). Palanisamy et al 23 recently demonstrated that propofol, at approximately 15 and 30 μM, for a 4 h exposure, did not induce rat primary NPC necrotic cell death and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies have focused on the anesthetic-induced type 1 cell death (apoptosis), 21,22 but cells can also die from type 2 (autophagic cell death) or type 3 cell death (necrosis). Palanisamy et al 23 recently demonstrated that propofol, at approximately 15 and 30 μM, for a 4 h exposure, did not induce rat primary NPC necrotic cell death and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of attenuation of the blood-retinal barrier by BMSCs were not determined in the present study. However, some stem cells have been found to produce genes mediating barrier properties [40], and adipose-derived stem cells prevented blood-retinal barrier leakage in diabetic rats possibly via differentiation into glial cells [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al showed that sevoflurane induced ER stress and activated autophagy, which protected against sevoflurane-induced apoptosis in H4 cells (Zhou et al, 2016). It also been suggested that isoflurane-induced increase in cleaved caspase-3 in the neonatal rat brain can be ameliorated by preconditioning with a brief anesthetic exposure (Peng et al, 2014). Consistent with these findings, it was proposed that adequate promotion of autophagy may play a protective role for cell survival by preventing developmental neurotoxicity of general anesthetics (Li and Yu, 2014).…”
mentioning
confidence: 99%